Hubungan Sanitasi Dasar dengan Kejadian Diare pada Balita Di Wilayah Kerja Puskesmas Pembina Kota Palembang - Apriani Endawati; Rico Januar Sitorus; Heru Listiono (Universitas Batanghari Jambi, 2021)
Diarrhea was the number one case of death in baby 31.4%, childhood 25% and The fourth in all age groups 13.2%. South Sumatera precisely in Seberang Ulu II is a sub district that has highest rate of diarrhea disease one of the located in the working of Pembina health center were have that 979 cases. The purpose of this study was to association basic of sanitation (toilet quality, lay-stall and waste water disposal) related the incidence of diarrhea on childhood. This Research use propositional stratified accidental sampling (cross sectional) study design. The sample was mother that has children under five years old (0-59 month) and their were 52 respondent. The data analysis that was done bivariate and univariate data. Bivariate analysis used Chi square test. The result showed that there was significant correlation between toilet quality (ρ value 0.004 ; OR 7; 95% Cl 2.012-24.358), laystall (ρ value 0.000;OR 13; 95% Cl 3,005-56,236) and waste water disposal (ρ value 0.000; OR 15,75; 95% Cl 3,601- 68,884) with diarrhea childhood. The conclusion that the distribution of the incidence of diarrhea was 15,75% and from all variable there was significant correlation with diarrhea in childhood. We suggest making latrines/toilet, constructing a simple covered garbage dumps and repair or making waste water disposal and optimizing environmental health socialization programs, namely prevention and control of disease.